The Absolute Age of Milky Way Globular Clusters - Jiaqi (Martin) Ying; Brian Chaboyer; Michael Boylan-Kolchin; Daniel R. Weisz; Rowan Goebel-Bain (The Astrophysical Journal, 2025)
Globular clusters (GCs) provide statistically significant coeval populations of stars spanning various evolutionary stages, allowing robust constraints on stellar evolution model parameters and ages. We analyze eight old Milky Way GCs with metallicities between [Fe/H] = −2.31 and −0.77 by comparing theoretical isochrone sets from the Dartmouth Stellar Evolution Program to Hubble Space Telescope (HST) observations. The theoretical isochrones include uncertainties introduced by 21 stellar evolution parameters such as convective mixing, opacity, diffusion, and nuclear reactions, capturing much of the quantifiable physics used in our code. For each isochrone, we construct simulated color–magnitude diagrams (CMDs) near the main-sequence turnoff region and apply two full-CMD-fitting methods to fit HST Advanced Camera for Surveys data across a range of distances and reddening and measure the absolute age of each GC from the resulting posterior distribution, which accounts for uncertainties in the stellar models, observations, and fitting method. The resulting best-fitting absolute ages range from ≈11.5 to 13.5 Gyr, with a typical error of 0.5–0.75 Gyr; the data show a clear trend toward older ages at lower metallicities. Notably, distance and reddening account for over 50% of the uncertainty in age determination in each case, with metallicity, α abundance, mixing length, and helium diffusion being the most important stellar physics parameters for the error budget. We also provide an absolute age–metallicity relation for Milky Way GCs.